The Concise Latest Report on the Advantages and Disadvantages of Pure Biodiesel (B100) on Engine Performance: Literature Review and Bibliometric Analysis - Muji Setiyo; Dori Yuvenda; Olusegun David Samuel (Universitas Pendidikan Indonesia, 2021)
Currently, many countries are promoting B100 as the main fuel for diesel engines towards the transition to 100% renewable energy applications. However, due to its properties, B100 has both advantages and disadvantages to replace diesel oil. Therefore, a bibliometric analysis was carried out to evaluate the performance and emissions of a diesel engine with the B100 being tested on a multi-cylinder diesel engine for cars. Unfortunately, only 12 of the 127 selected articles are eligible to be reviewed in detail and none of them discusses all the key performance of diesel engines which include Brake Thermal Efficiency (BTE), Specific Fuel Consumption (SFC), Cylinder Pressure (CPs), Heat Release Rate (HRR), NOx, and smoke. Through data synthesis, we found that the use of B100 provides advantages in engine noise, thermal efficiency, specific fuel consumption, and emissions under certain engine loads. On the other hand, it also has the potential to result in poorer performance, if there is no modification to engine components and the addition of additives. As a recommendation, the results of this analysis provide a guide for further research to examine the use of B100 with all diesel engine performance variables. Research paths can be developed with the wider potential to provide new arguments on various diesel engine technologies, engine capacities, B100 raw materials, and test environments.